Secure cluster head selection in wireless sensor networks using fuzzy based generic algorithm - Dhipa, M.; Sampath, Nithya; Seetha, R.; Nageswari, D. (Wireless networks, 2025)
Wireless Sensor Networks (WSN) has made an indelible mark on the lives of everyone by assisting in agriculture, education, manufacturing, and environmental monitoring etc. One of the biggest problems for WSNs is achieving security and protecting data in a hostile environment against nodes. To address these problems, a novel Reliable Fuzzy based Generic Detection (RFGD) method has been proposed in this paper. The suggested RFGD framework consists of 2 stages. Initially, a reliable cluster head is selected by using the Parameter Optimized Fuzzy Model. Secondly, a Generic Detection method is used to detect compromised nodes to ensure secure transmission of data. The proposed RFGD technique is equated with state-of-arts techniques in terms of packet delivery ratio, energy consumption, number of alive nodes and detection accuracy. The proposed RFGD framework achieves 26.66%, 10.76%, 17.43% and 10.76% more detection accuracy than ACOPSO improved ABC, FGF and GAPSO-H methods.